(untitled) (Al-Academy, 2025)
The research is interested in studying the method of design construction in forming the conceptual art of artistic works that are based on the artist, as it is the source of sensory inputs and outputs and basic data in shaping the artistic visual experience within the designed structures of the artistic work through transformations that change the pattern of direction that the artist works on, and it appears to us an emotional art that elevates the aspects of reality by adapting them for purposes. The artist’s personal and aesthetic vision to present a new vision as a living space that takes on the character of the living world dominated by absurdity, which the artist tried to express, abandoning traditional aesthetic standards and moving away from his original function in light of globalization and technological progress the research included four chapters. In the first chapter, the researcher addressed the research problem that lies in answering the question: - What is the design structure style of conceptual art? The researcher touched on the importance of this research, which lies in studying the methods of design structure for conceptual art by defining and clarifying them and knowing their intellectual and aesthetic data. The goal of the research is: revealing the methods of design structure for conceptual art? The second chapter included two sections. The first section was entitled Methods of design construction of artistic works, while the second section was titled Design construction in the formation of conceptual art. The third chapter included the research community, which were the works of international artists. The research sample was chosen randomly because the community was homogeneous. Their number reached (20) works of art, who were selected from the research community for the purpose of achieving the goal. The researcher adopted a tool to measure the design construction style. For conceptual art, which relied on the indicators of the theoretical framework, the researcher carried out validity and reliability measures on it. The results showed: The mechanism of operation of design structural methods in conceptual art, which is subject to mental and intellectual calculations linked to the function of the design achievement, which codifies the designer’s activities within the framework of the intended goal. The researcher concluded conclusions, including: Design has a role in the style of the design structure of conceptual art in the process of building new forms with modern materials and techniques, which established and confirmed the artist’s harmony with reality.